IMPLEMENTASI IPAS UNTUK MENUMBUHKAN KEPEDULIANTERHADAP KEBERSIHAN LINGKUNGAN - Nur, A. Muafiah; Aulia, Reski; Mutmainnah, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Twenty-first-century education requires students not only to master cognitive aspects but also to develop critical, creative, and collaborative thinking skills, as well as environmental awareness. Natural and Social Sciences Learning (IPAS) serves as an important medium for instilling environmental care values from an early age, especially in elementary schools. This study aims to describe the role of IPAS learning in fostering environmental care attitudes among third-grade students at SDN 74 Bontorita II. The research employed a qualitative descriptive method using observation, interviews, and documentation techniques. The results indicate that prior to the implementation of IPAS learning, students’ level of environmental awareness was relatively low, as reflected in a lack of awareness in disposing of waste properly and minimal participation in cleanliness activities. After the implementation of environment-based IPAS learning through observation activities, hands-on practices, and simple projects such as poster creation and classroom clean-up actions, a significant improvement in environmentally caring behavior was observed. Improvements were seen in proper waste disposal (from 40% to 85%), understanding of waste types (from 35% to 90%), participation in cleanliness activities (from 30% to 80%), and independence in maintaining cleanliness (from 45% to 88%). These findings indicate that contextual and project-based IPAS learning is effective in fostering environmental awareness and students’ social responsibility. Therefore, IPAS learning plays an important role in shaping environmentally caring character among elementary school students.